KOMPETENSI NOTARIS DALAM MENJALANKAN PERAN, TUGAS DAN KEWENANGAN PADA PERBANKAN SYARIAH: STUDI PADA BANK PERMATA SYARIAH - Rina Taurina; Endang Purwaningsih; Irwan Santosa (LPPM Universitas Bina Bangsa, 2023)
The growth of the Islamic banking industry is growing amid increasing public awareness of banking which is in accordance with Islamic law. This is an opportunity as well a challenge for a Notary as an official who makes an authentic deed in his role in Islamic bank. This study analyzes the implementation of sharia principles as a guide for Notaries in making the construction of sharia banking contract to comply with the mandate of Sharia Banking Law and Fatwa of National Sharia Council. Furthermore, the main point is the competence of Notaries in in carrying out their roles, duties and authorities in Islamic Banking. The research method used is empirical normative through interviews with Islamic banking and the Indonesian Notary Association and National Sharia Council. It is concluded that Notary has a strategic role in the application of sharia principles so that the deed is in accordance with normative law and guarantees legal certainty and the value of justice. Competence in understanding philosophical and practical aspect is absolutely needed and Notaries are required to improve their insight and competence related sharia contracts. The legal vacuum in terms of their authority in making sharia deeds, especially banking becomes an obstacle in the implementation of the Notary’s role. UUJN and Sharia Banking Law, do not contain a clause regarding the authority of Notary. The government as regulator is responsible for creating legal products to ensure legal certainty and justice